The restitution of Roman Catholic Church land to indigenous people in post-apartheid South Africa: 1994–2014 - Lephoto, Mokone B. (HTS teologiese studies, 2020)
The political and legal perspectives on and understanding of the process of land reform in South Africa differ from the church’s vision and understanding on what land reform entails. Currently, land reform through the restitution of church land to indigenous people is still not solved to all party’s satisfaction, although this issue is on the table since 1994. The research focuses on the actions by the Roman Catholic Church that argued that ‘society ensures justice when it provides the conditions that allow associations or individuals to obtain what is their due, according to their nature’ (O’Neil & Black 2004; O’Brien & Shannon 2006). The church also suggests that land is an arable resource that gives people access to certain basic needs necessary for them to lead a dignified life. This article discusses and evaluates the outcomes of the restitution of Catholic Church land since 1994–2014. It also addresses the contribution by the Catholic Church to land restitution during the period of 1994 –2014 to advocate and encourage further participation in the land reform programme. In light of this reality, one can ask whether the Catholic Church can bring about positive influence to the present challenges facing the land reform programme. Positive examples of the trainings and workshops conducted by the church within different communities are showcased to note possible future structures for dealing with land restitution from the church’s perspective.